RELATIONSHIP BETWEEN HYPERTENSION AND COVID-19 DEATHS, CASE CONTROL STUDY - Elviza Rahmadona; Helda; Musfardi Rustam (Universitas Islam Negeri Alauddin Makassar, 2022)
One of the most comorbidities to Covid-19 patient in Indonesia is hypertension, which is 52,1% in confirmed cases and 19,2% in mortality cases and be ranked first of comorbidities in Covid-19 patient. This study was aimed to determine association hypertension to Covid-19 patient death for April 2020 – July 2021 based on medical record data of inpatient at RSUD Arifin Achmad – Riau Province. Methods This is a case control study, which is cases were the death patient and controls were non-dead patient based on medical record data through SIMRS app. This study analyze 93 cases and 200 controls include in inclusion criteria which has been tested PCR. The data was analyzes use chi-square test and logistic regression. Result Based on the result, that was found association between hypertension to mortality of covid-19 but have protective risk to patient in adjusted OR = 0,0661 (95% CI = 0,026 – 0,171, p value <0,0001) after controlled by age, sex, diabetes, COPD, CVD and domicile. This study result have limitation yet that is misclassification non differential and available data in medical record patient through SIMRS app so it didn’t have any strong association. A low association was found between hypertension to mortality of Covid-19 with OR adjusted = 0,0661 (95% CI = 0,026 – 0,171, p value = <0,0001) in inpatient at RSUD Arifin Achmad Province of Riau after controlled by age, sex, diabetes, COPD, CVD and domicile.